Pendampingan Kemampuan Pengusaha Untuk Menentukan Biaya Variabel Dalam Meningkatkan Profitabilitas Pada UD. Agus Sitah Kikil Lembu di Huta III Sahkuda Bayu, Simalungun - Agung Yudha Permana; Helmi Rivai Nasution; Elsa Putri Utami; Septia Pratami Nur Rizki; Elfina Okto Posmaida Damanik (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
One of the activities of the Faculty of Economics Management Study Program at the University of Simalungun is Community Service. Where, in this case it is conveyed that this is an assignment activity from the Cost Accounting Management course. Here, it can be seen that this community service is assisting entrepreneurs' ability to determine variable costs in increasing profitability at UD. AGUS SITAH Kikil Lembu in Huta III Sahkuda Bayu, Simalungun. We do this assistance so that Ox Pebble Entrepreneurs can increase profitability by including variable costs in the income statement. Here we introduce and apply variable costs to the income statement that can help entrepreneurs. The methods we use in making this journal are interview and qualitative. In this activity we also have several important stages such as, Planning Stage, Observation Stage, Training and Mentoring Stage, and Reporting Stage. Here it is known that the results during this activity run effectively and efficiently.